Analysis and Design of E-Commerce Information Systems Using the User Centered Design Method at PT. Pure Healthy Nature - Amelia Andi; Yakub Yakub (Tech-E, 2019)
PT.Murni Alam Sehat is one of company sell medical device and medicine by prescription or without doctor’s prescription. The problem in marketing department in this company do not have promotion media for offer the products to consumer, no online sell, and order only by phone. To solve the problem in marketing department is build up e-commerce system. E-commerce system use Unifed Modelling Languange (UML); Activity Diagram, Use Case Diagram, Sequence Diagram, and Class Diagram. User Centered Design (UCD) as design method. Program language for e-commerce system is PHP and MySQL for database. The result of research is a e-commerce system website base to help search information product, company could get report easier, consumer can do purchase by online everywhere and everytime.